L'"économie" de la formation - Xavier Zunigo (Les éditions de la Maison des sciences de l'Homme, 2005)
Studies have shown that block-release training offer more knowledge of working environment than they actually provide technical skills. Although this remains true, this paper explores ways in which the functioning and the constraints of the training market influence both the practice and the contents of the actual training. An analysis of the importance granted to relations with firms, and the resulting reduced leeway for trainers, and of the low-skilled positions which this type of training leads to, shows that training essentially takes the form of a foundation course on attitudes and behaviour in working environments. However, the program does not aim to create an obedient workforce. Rather, the training serves the interests of both firms and trainees. It thus constitutes a community of interests that ultimately serves the interests of the training organism as well, permitting it to continue to survive in the training market.